The pre-crime society : crime, culture and control in the ultramodern age - Arrigo, Bruce A.; Sellers, Brian G. (Bristol University Press, 2021)
We live in a pre-crime society where technological strategies and techniques are employed to achieve hyper-securitization. Exploring theories, technologies and institutional practices, this pioneering book explains how the pre-crime society operates in the 'ultramodern' age and proposes new directions in crime control policy.